A pilot study of anti‐nephrin antibodies in podocytopaties among adults - Chebotareva, Natalia; Vinogradov, Anatoliy; Birukova, Yevgeniya; Alentov, Igor; Sergeeva, Natalia; Chemodanova, Daria; Kononikhin, Alexey S.; Moiseev, Sergey V. (Nephrology (Carlton, Vic.), 2024)
Aim Minimal change disease (MCD) and focal segmental glomerulosclerosis (FSGS) are podocytopathies characterized by damage to the glomerular filtration barrier, leading to proteinuria and nephrotic syndrome. The production of anti‐podocyte antibodies has been proposed as potential circulating factors contributing to the development of these conditions. The aim of the study is to evaluate the levels of anti‐nephrin antibodies in patients with podocytopathies and healthy subjects. Methods In this study, a total of 77 patients with active glomerulopathy and 11 healthy subjects were included. Forty one patients were diagnosed with FSGS, 11 with MCD, and 25 with MN. To measure the levels of anti‐nephrin antibodies, enzyme‐linked immunosorbent assay was used. Results The levels of antibodies to nephrin were significantly higher in patients with MCD 61.2 [28.9–66.3] ng/mL and FSGS 32.5 [17.2–58.4] ng/mL compared to MN 20.3 [14.4–38.4] and healthy individuals 15.3 [12–18.9] ng/mL, p < .05. In patients with primary FSGS, the levels of antibodies to nephrin were significantly higher 45.2 [20–64.3] ng/mL compared to patients with secondary FSGS 26.7 [11.2–44.1] ng/mL, p < .05. There were no significant differences in the remission rate between the anti‐nephrin antibodies positive and negative groups (log‐rank test: p = .158). Conclusion The level of anti‐nephrin antibodies was found to be significantly higher in patients with MCD and pFSGS compared to those with sFSGS, MN, and healthy subjects. Anti‐nephrin antibodies in MCD and primary FSGS may be associated with the severity of podocytopathies, however they did not have an impact on the response to therapy. Summary at a glance The level of anti‐nephrin antibodies in adults was found to be significantly higher in patients with MCD and FSGS compared to those with secondary FSGS, MN, and healthy subjects. Anti‐nephrin antibodies may be associated with the pathogenesis of MCD and primary FSGS. However, anti‐nephrin antibodies did not have an impact on the response to immunosuppressive therapy.